1998
DOI: 10.1097/00007890-199803270-00010
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Endothelial Expression of Human Cd59 Prolongs Heart Function in an Ex Vivo Model of Xenograft Rejection

Abstract: High-level endothelial-specific expression of CD59 was effective in prolonging the function of mouse hearts perfused with 20% human plasma, whereas low-level, broader expression did not provide protection from 6% plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 24 publications
1
10
1
Order By: Relevance
“…We generated human CD59 (hCD59) transgenic mice that selectively express the transgene in erythrocyte ( ThCD59 RBC ) or in endothelium and some hematopoietic cells such as platelets (Supplemental Figure I), neutrophils, and monocytes ( ThCD59 END ) as previously described 25, 26 . In these transgenic strains, over-expression of hCD59 is effective in providing additional protection against mouse complement 25, 26 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We generated human CD59 (hCD59) transgenic mice that selectively express the transgene in erythrocyte ( ThCD59 RBC ) or in endothelium and some hematopoietic cells such as platelets (Supplemental Figure I), neutrophils, and monocytes ( ThCD59 END ) as previously described 25, 26 . In these transgenic strains, over-expression of hCD59 is effective in providing additional protection against mouse complement 25, 26 .…”
Section: Resultsmentioning
confidence: 99%
“…We generated human CD59 (hCD59) transgenic mice that selectively express the transgene in erythrocyte ( ThCD59 RBC ) or in endothelium and some hematopoietic cells such as platelets (Supplemental Figure I), neutrophils, and monocytes ( ThCD59 END ) as previously described 25, 26 . In these transgenic strains, over-expression of hCD59 is effective in providing additional protection against mouse complement 25, 26 . To study the role of CD59 and complement in atherosclerosis in the context of a favorable pro-atherogenic environment, mCd59ab −/− and Apoe −/− mice were crossed to generate mCd59ab −/− / Apoe −/− , and ThCD59 END+/− and Apoe −/− mice to generate ThCD59 END+/− /Apoe −/− mice (Supplemental Figure II, A-C online).…”
Section: Resultsmentioning
confidence: 99%
“…However, the importance of preformed xenoreactive antibodies to non-Gal antigens remains to be determined. Previous studies have suggested that if the response of anti-Gal antibodies was eliminated, that grafts expressing high levels of complement regulatory proteins survived longer than wild-type pig organs (38) (39) (40) (41) (42). Since the major target or targets of non-Gal antibodies has not been determined, immunoadsorbtion of the xenoreactive antibodies seems impractical at this time.…”
Section: Discussionmentioning
confidence: 99%
“…The hCD59 in hCD59 ICAM-2+/− mice is selectively expressed in endothelial cells, macrophages, and platelets19. In these transgenic strains, over-expression of hCD59 is effective in providing additional protection against mouse complement18, 19. We crossed each of the two strains with ApoE −/− mice (B6 background, Jackson Laboratory) to produce mCd59ab −/− /ApoE −/− and hCD59 ICAM-2+/− /ApoE −/− mice, respectively.…”
Section: Methodsmentioning
confidence: 99%